Gender Differences in Depression: Evidence From Genetics - Zhao, Lihong; Han, Guanghong; Zhao, Yinghao; Jin, Yang; Ge, Tongtong; Yang, Wei; Cui, Ranji; Xu, Songbai; Li, Bingjin (Frontiers in Genetics, 2020)
Compared with men, female depression accounts for a larger proportion. Behavioral genetics researches find gender differences in genetic underpinnings of depression. We found that gender differences exist in heritability and the gene associated with depression after reviewing relevant research. Both genes and gene-environment interactions contribute to the risk of depression in a gender-specific manner. We detailed the relationships between serotonin transporter gene-linked promoter region(5-HTTLPR) and depression. However, the results of these studies are very different. We explored the reasons for the contradictory conclusions and provided some suggestions for future research on the gender differences in genetic underpinnings of depression.